Exploring the elastocaloric effect of Shape Memory Alloys for innovative biomedical devices: a review (Fracture and Structural Integrity, 2024)
This paper discusses Shape Memory Alloys’ (SMA) elastocaloric effect (EC) and underscores its potential use in substituting conventional cooling systems, for future and innovative applications in the biomedical sector, where temperature has a significant influence on the structure and function of crucial macromolecules and cells. After an introduction on SMA’s EC and its relevance for medical and biomedical field, the authors examine the principles and mechanisms at the base of this particular property, with a focus on main keys essential to evaluate performances and the differences characterizing most used elastocaloric alloys, also exploring strategies currently in place to improve performances. Thereafter, the discussion moves on the current design and development of instruments exploiting this innovative behavior, introducing thermal microdevices made of elastocaloric materials in biomedical applications. It concludes by analyzing future directions of elastocaloric cooling and heating for biomedical applications, including possible upcoming medical and biomedical devices, evaluating challenges that researchers still need to address for the adoption of SMA’s EC in the biomedical field.
Keywords: SMA; innovative applications; elastocaloric effect; thermal microdevices; compact refrigeration